Implementasi Model Pbl Dan Nht Pendekatan Tpack Untuk Meningkatkan Aktivitas Dan Berpikir Kritis Siswa SD - Tri Mustika S; Radiansyah (CV. ITTC INDONESIA, 2024)
Low levels of activity, critical thinking skills, and learning outcomes in science education are the problems raised in this research. This research used Classroom Action Research (PTK) which was carried out four meetings. This research was attended by fourteen fourth grade students at SDN Tabunganen Kecil, consisting of five girls and nine boys, in the second semester of the 2023/2024 academic year. Based on the findings of this research, teacher activity scores increased from 24 in meeting 1 to 32 in meeting 4. The level of student engagement increased from 36% in meeting 1 to 100% in meeting 4. On the other hand, the percentage of critical thinking skills increased from 36% in meeting 1 to 93% in meeting 4. The percentage of students who achieved classical mastery of learning outcomes increased from 36% meeting 1 to 93% meeting 4. Utilization of PBL and NHT models, in addition to the Video-Based TPACK Approach, can improve student learning outcomes, teacher activity, and critical thinking skills, according to with the findings of this research.